KARAKTERISTIK LINGKUNGAN BEHAVIORISTIK DALAM MENGEMBANGKAN KETERAMPILAN BERBAHASA ARAB PADA MARKAZ LUGHOH DI PONPES AL-ITTIFAQIAH - Awaliyah, Rofikotul; Yuniar; Nurul Hidayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of a behavioristic environment in Arabic language learning at the Markaz Lughoh of Al-Ittifaqiah Islamic Boarding School and to analyze its impact on students’ language skill development. This research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, then analyzed descriptively based on behavioristic theory as the main conceptual framework. The results show that the Markaz Lughoh consistently applies core behavioristic principles such as stimulus-response, reinforcement, repetition, and modeling. Intensive habituation in using Arabic, supported by a reward and punishment system, successfully shaped positive and sustainable language behavior. The implementation of this strategy significantly improved students’ four Arabic language skills kalam (speaking), istima’ (listening), qira’ah (reading), and kitabah (writing) and fostered a disciplined, active, and communicative learning environment. Thus, the application of a behavioristic environment at Markaz Lughoh has proven effective in holistically enhancing students’ Arabic language competence.